Bioenergetic and redox signaling in hepatic steatosis models: Integrative analysis of nutritional, hormonal, and inflammatory stimuli - Kakimoto, Pâmela Aiako Hypólito Brito (2021)
Non-alcoholic fatty liver disease (NAFLD) is a term comprising a spectrum of liver diseases in which lipids accumulate in the hepatocyte cytoplasm, ranging from simple steatosis to steatohepatitis, and fibrosis. Commonly found in obese individuals and type 2 diabetic patients, NAFLD prevalence is growing globally, and currently there are no approved treatments to prevent its progression. In the center of hepatic lipid metabolism are mitochondria, and the comprehension of their functional response to nutrient overload is vital to map disease development. Moreover, oxidant production is altered in obesity and stimulated by lipidic overload and the activation of pro-inflammatory pathways. Since cellular redox state is fundamental in the control of mitochondrial function and that the activity of many metabolic and signaling enzymes susceptible to oxidative modifications, understanding the action of oxidants is a critical step to uncover the pathophysiological mechanisms of diet-associated metabolic diseases . In this thesis, we propose to evaluate whether redox signaling participates in metabolic changes promoted by lipidic overload using in vivo and in vitro approaches. In the first part, we characterized, in C57BL/6NTac wild type mice and knockout for the enzyme inducible nitric oxide synthase (iNOS) submitted to 2, 4, and 8 weeks of high-fat feeding, that hepatic mitochondrial function is sustained over the time, independently of the diet, iNOS status, adiposity, and systemic insulin sensitivity. In the second part, we characterized, in hepatocyte cell lines, how ATP sources are affected by overload of palmitate, a saturated fatty acid. We identified that glycolytic ATP production is acutely activated by palmitate and modulated by oxidant production. Furthermore, mitochondrial ATP production is sustained under extensive oxidative stress and mitochondrial fragmentation. Using selective inhibitors, we found that the production of superoxide and/or hydrogen peroxide at the IQ site of respiratory mitochondrial complex I is associated with the metabolic rewiring promoted by palmitate. We demonstrate that increased glycolytic flux linked to mitochondrially-generated redox imbalance is an early bioenergetic result of palmitate overload and lipotoxicity. In conclusion, we identified, in two different steatosis models, that mitochondrial function can resist many insults and still sustain ATP production. Its notorious dysfunction in the fatty liver is probably not causative, but rather a downstream target of toxicity.